Effect of Age and Gender on QRS Complex Amplitude in Healthy Adults. - Yasir M. Khaleel; Baybeen K. Al-Selevany; Muzahim F. Mahmood (مجلة كلية الطب, 2014)
Background: There is controversy about the upper normal value of QRS complex amplitude in adult population under the age of 40 years. Most of the left ventricular hypertrophy voltage criteria were designed or tested for people above 40 years. In addition to age, QRS amplitude is also affected by gender and racial factors.